Revision Total Ankle Replacement using the Inbone 2 System, Nottingham Experience. Issue 4 (22nd October 2020) - Salem-Saqer, Hatem; Raglan, Martin; Dhar, Sunil
Category: Ankle Arthritis; Ankle Introduction/Purpose: The Inbone Total Ankle Replacement System (Wright) is a modular stemmed ankle replacement, it is marketed as for both primary and revision TAR, it has been in use at Nottingham since 2016 mainly for revisions, we are reporting our experience with this system and our early results. Methods: This is a retrospective study with prospective collected data. We identified 27 (18M/9F) patients who had Inbone 2 TAR for revision surgery during the period August 2016 -March 2019. The mean follow up was 21 months (7-38months). Mean age of 69 years (51-81).All ankle revisions were a single-stage revision apart from 1 patient who had a 2 stage revision as at the first stage infection was suspected, it was left with a cement spacer and when all samples came back negative the second stage was carried out.All patients had follow up appointments at 6 weeks, 3, 6 and 12 months. Patients were required to fill in MOXFQ questioner and all had weight-bearing radiographs on every follow up appointment.The indication for the surgery was aseptic Loosening 23, Malalignment 1 Insert wear 2 and heterotopic ossification 1. Results: 20 patients had concurrent procedure during the surgery(Table 1). There was 1 deep wound infection that required DAIR procedure 3 weeks after the revision surgery and has gone to make full recovery, no other complication were reported.Improvement in clinical outcome and PROMS data was noted on follow up, MOXFQ for Pain improved from 70 pre op to 34 at 6 months and 32 at 1 year(p<0.001 paired t test), The outcome for Walking improved from 69 pre op to 41 at 6 months and 40 at 1 year(p<0.001 paired t test).Radiological alignment was maintained in all ankles both in the coronal and the sagittal plain, posterior heterotopic ossification was noted in 8(29%), No loosening or signs of failure at any follow up appointment Conclusion: This is one of the largest series of this implant used in revision TAR. Our early results show considerable improvement in patient outcomes with very low complications and no failures.This implant provides a good option as a revision implant and our view that it is a superior solution to ankle fusions for failed total ankle replacements